Impact of Financial Deepening on Economic Growth in Nepal - Mani Upadhyaya, Yadav; Raj Kharel, Khom; Poudel, Omkar; Acharya, Pradeep (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: The objective of this study is to investigate the relationship between financial deepening and economic growth in Nepal. Design/methodology/approach: The long-term and short-term dynamics among the variables are assessed using econometric techniques. Granger causality tests are applied to determine the direction of causality between private sector credit and economic growth. Findings: The findings reveal a significant long-term equilibrium relationship among the variables. Both broad money and private sector credit have a positive impact on economic growth in Nepal. The Granger causality tests show bidirectional causality between private sector credit and real gross domestic product. Conclusions: The results highlight that both broad money and private sector credit contribute significantly to economic expansion. Implications: The robustness of the model, confirmed through diagnostic tests, underscores the critical role of financial sector policies in sustaining Nepal’s economic growth. JEL Classification: O16, O43, E44, F43, O53